Rethinking Securities in an Emergent Technoscientific New World Order : Retracing the Contours for Africa's Hi-jacked Futures - Nhemachena, Artwell; Mawere, Munyaradzi (Mankon, Bamenda [Cameroon] : Langaa Research & Publishing CIG, 2018)
The emergent technoscientific New World Order is being legitimised through discourses on openness and inclusivity. The paradox is that openness implies vulnerability and insecurities, particularly where closure would offer shelter. While some actors, including NGOs, preach openness of African societies, Africans clamour for protection, restitution and restoration. Africans struggle for ownership and access to housing, for national, cultural, religious, economic, and social belonging that would offer them the necessary security and protection, including protection from the global vicissitudes and matrices of power. In the presence of these struggles, to presuppose openness would be to celebrate vulnerability and insecurities. This book examines ways in which emergent technologies expose Africans and, more generally, peoples of the global south to political, economic, social, cultural and religious shocks occasioned by the coloniality of the global matrices of power. It notes that there is the use -- by global elites -- of technologies to incite postmodern revolutions designed to compound the vicissitudes and imponderables in the already unsettled lives of people north and south. Particularly targeted by these technologies are African and other governments that do not cooperate in the fulfilment of the interests of the hegemonic global elites. The book is handy to students and practitioners in security studies, African studies, development studies, global studies, policy studies, and political science.
The development of (neo- )imperial sacrifice, global atavism and African insecurities : an introduction / Artwell Nhemachena & Munyaradzi Mawere -- "Ethnicity", "nomadic" identities and (in- )securities in africa : the case of the Tsonga speaking people in South Africa / Artwell Nhemachena & Dolphin Mabale -- Disabilities and human insecurities : women and oculocutaneous albinism in post-colonial Zimbabwe / Fidelis Peter Thomas Duri & Alice Makama -- A religious survey of technological oddity : humanoid as a case study / Raymond Ogunade & Gbenga Zaccheaus -- The vacuity of the responsibility to protect in Africa? Insecurities and social protection in Zimbabwe / Clement Chipenda & Tom Tom -- Entangled in the "new world order" : Africa's (in- ) security quandaries and prospects / Aluko Opeyemi Idowu -- Rethinking security and global politics : the tethering of Africa in an era of globalisation / Munyaradzi Mawere & Costain Tandi -- United Nations agencies and management of humanitarian crisis of internally displaced persons (IDPS) in Nigeria's Abuja camps : reflections on the security of Igbo migrants in the north (2010-2016) / Orji Boniface Ifeanyi -- Religions and insecurities : heritage contestations and religious praxis in Mberengwa and Masvingo, Zimbabwe / Dube Edmore -- Electoral politics and (in- ) securities in Africa : thinking the past and the present for the future of Africa / Costain Tandi & Munyaradzi Mawere -- Espousing global "civilisation" in "social networking" : linguistic vulnerability and techno-paranoia among Tshivenda/Xitsonga Speakers in Zimbabwe / Prosper Hellen Tlou & Aleck Mapindani -- Zimbabwean youths and the insecurities from "bronco" abuse / Nancy Mazuru -- Democracy, political dynamics and (in- )security in the global south : hard lessons for Africans / Misheck P. Chingozha & Munyaradzi Mawere -- The role of corporate social responsibility in curbing insecurity in Nigeria's Niger Delta Region / Chioma Elizabeth Abuba -- Should the west keep on playing God? Genetic engineering, bio-technological insecurities and their implications for Africa / Tapuwa Raymond Mubaya -- Freedom to become insecure? vulnerabilities from the emergent digital media in Zimbabwe / Last Alfandika; Gift Gwindingwe & Golden Maunganidze.
Includes bibliographical references.
Print version record.
JSTOR
Keywords: Globalization -- Africa; Technological innovations -- Social aspects -- Africa; Technology -- Social aspects -- Africa; Mondialisation -- Afrique; Innovations -- Aspect social -- Afrique; BUSINESS & ECONOMICS / Industries / General; SOCIAL SCIENCE / Regional Studies; Globalization; Technological innovations -- Social aspects; Technology -- Social aspects; Africa